A Comparative Study of Owner-Manager Personal Values in Black and White Small Businesses - Watson, John G.; Simpson, Leo R. (Academy of Management Journal, 1978)
The authors discuss research they conducted that examined the personal value orientations of black and white owner-managers of small business firms. The authors note that the personal values of managers often has an influence on the compatibility between employees and management. They also suggest that a study of values in the organizational setting allows for greater interdisciplinary collaboration than a study of attitudes. They found that there were no significant differences in the personal value orientation of black and white managers and that these orientations did not differ from managers in large business firms. They note that significance of these findings because pervious notions held that black managers in large organizations only got there because they epitomized white values.